Pewarisan Budaya Bali Aga dalam Tradisi - I Putu Mardika (Pramana: Jurnal Hasil Penelitian, 2022)
The Bali Aga community in Pedawa Village, Banjar District has the Saba Nguja Benih Tradition. This ritual is held at the village temple on the full moon of Sasih Kaulu every five years. Nguja Benih are believed to be a form of respect for Dewi Sri so that the glorified seeds can thrive. This article analyzes two things. Namely, how is the process of cultural inheritance in the Nguja Benih Tradition both formally and informally. Then this article also analyzes the media of inheritance through the jejumputan dance which accompanies the Saba Nguja BenihTradition in Pedawa Village. This qualitative study is based on data collected through observation, interviews, and literature study. As a result, Saba Nguja Benih are passed down from generation to generation across generations from children to adults through enculturation and socialization. Socialization is carried out both formally and informally. Jejumputan dance is part of the Saba Nguja Benih Ceremony procession. This dance is performed by children who have not reached puberty. This dance is a cultural identity of the Pedawa people and must be danced during Nguja Benih to please Dewi Sri.